2019
DOI: 10.1109/access.2019.2937583
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Pedestrian Choice Behavior of Vertical Walking Facilities in Rail Transit Station Considering Reminder Sign

Abstract: A pedestrian choice model of vertical walking facilities based on random forest is established in rail transit station considering four key influence factors: interlayer height, luggage, the difference in the number of pedestrians in front of elevator and stairway, and walking speed. This model is verified with the collected data of Changchun light-rail transfer station and Beijing Xi-zhi-men railway transfer station, China, and compared with the choice model based on support vector machine. Prediction results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In particular, the research on the pedestrian exit choice has become a very important topic in this field. Li et al [38] established a pedestrian choice model of vertical walking facilities based on random forest and indicated that the effect of reminder sign can improved the efficiency of pedestrians passing. Cao et al [39] proposed an extended multi-grid model to study fire evacuation in a two-exit room and investigated the exit selection based on random utility theory.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the research on the pedestrian exit choice has become a very important topic in this field. Li et al [38] established a pedestrian choice model of vertical walking facilities based on random forest and indicated that the effect of reminder sign can improved the efficiency of pedestrians passing. Cao et al [39] proposed an extended multi-grid model to study fire evacuation in a two-exit room and investigated the exit selection based on random utility theory.…”
Section: Introductionmentioning
confidence: 99%